Appointment planning outpatient clinics and diagnostic facilities - Zonderland, Maartje E. (SpringerBriefs in Health Care Management and Economics, 2014)
Appointment Planning in Outpatient Clinics and Diagnostic Facilities provides a concise overview of the medical and mathematical aspects of appointment planning in healthcare. This SpringerBrief specifically focuses on outpatient clinics and diagnostic facilities. It begins by introducing the topic from a medical perspective, discussing the kinds of clinics and facilities that are out there, while exploring the appointment systems they use and the problems they face. Next, the mathematical aspects of appointment planning are examined, including Markov decision modelling, queueing theory, etc. Subsequently the book addresses implementation issues that may arise, whether they be technical, medical or cultural. Finally Appointment Planning in Outpatient Clinics and Diagnostic Facilities provides an outlook on the appointment systems of the future and what they will require as a consequence of current and future developments in the medical sector.